Training for improved vertical jump - Kraemer, W. J.; Newton, R. U. (Sports Science Exchange, 1994)
Explosive strength is a characteristic of performance that is common in many sporting endeavors. However, training very frequently includes reduced velocity "strength" training which develops capacities which are only appropriate for a very few activities (e.g., power lifting). The Contribution of Muscular Strength: Heavy strength training is of little benefit to already strong individuals who wish to perform explosive movements. Power to Weight Ratio: It is the type of training that is important. A change in muscle structure, such as that which can be developed through heavy weight training, should be accomplished prior to the commencement of specific explosive power training. Stretch-shortening Cycle: Training for explosive power must include activities which maximize the stretch-reflex phenomenon in the preparatory phase of any movement. Coordination of Movement Pattern: Specific skill coordination, the reduction of internal antagonist muscle forces, and the maximization of agonistic muscle contraction and speed can only be accomplished by training on the actual activity itself. Resistive Load: The maximum added resistance or load to an activity should be 30% of 1 RM. Plyometric/Drop-jump Training: Plyometric training places considerable strain on the musculo-skeletal system. It should be preceded by a standard weight training program until substantial improvements in performance are demonstrated (e.g., for vertical jumps be able to squat lift 150% of body weight). Weight Training: There is a suggestion that perhaps a combination of plyometric and light-weight training may provide the greatest stimulus for explosive power development. Periodization or When to Use Particular Forms of Training: The initial basic preparation period should involve weight training to increase muscle mass and strength. Activities should be whole-body as well as for specific muscle groups. In the pre-competition phase, heavier and more specific weight training can be initiated to emphasize maximal strength. The concentric contraction phase of each exercise should be as explosive as possible. Just prior to the competition phase, specific neural training is desirable. Heavy weights should be reduced and alternated with methods that emphasize rapid force development, high contraction velocities, use of the stretch-shorten cycle, and specific skill movements. During the competition phase, plyometric training should be removed or largely reduced. Strength and power maintenance can be achieved by training only twice per week. All training should cease 5-6 day prior to the competition to allow complete recovery to occur. A table shows the efects of different training forms on factors of explosive power. (see also http://www-rohan.sdsu.edu/dept/coachsci/vol21/kraemer.htm)